Postpartum depression crisis since the second lockdown and 'screening paradox': many women identified, very few treated - Magdalena Chrzan-Dętkoś; Tamara Walczak-Kozłowska (BMC, 2022)
Abstract Objective Exposure to stressful situations, such as emergencies, infectious diseases, and natural disasters, may lead to a heightened risk of perinatal mental health problems. Declared on March 11th, 2020, the global COVID-19 pandemic triggered an additional burden on women in the perinatal period. Safety recommendations, such as social distancing and isolation, were opposite to the usual advice given to new mothers. Besides fear, changes in financial stability and daily life reorganization contributed to increased depressive symptoms. As the periods of epidemic waves and lockdowns were associated with a more significant burden for young families, we aimed to assess the intensification of depressive and anxiety symptoms during the pandemic concerning the time intervals of the three lockdowns introduced in Poland. Methods: 1588 postpartum women took part in the online self-assessment with the Edinburgh Postnatal Depression Scale (EPDS) and General Anxiety Disorder 2 (GAD-2) questionnaire between January 1, 2020, and March 31, 2021. This self-screening is a part of a prevention program The Next Stop: Mum, implemented in the North of Poland. Results The highest severity of PPD symptoms and anxiety were observed during the second lockdown in Poland: the mean score in the EPDS and anxiety assessment was significantly higher than the mean scores from previous pandemic periods. Since the second lockdown, the average EPDS and GAD-2 scores remained similarly high. Moreover, with the duration of the COVID-19 pandemic, the percentage of women with elevated symptoms of postpartum depression and anxiety began to increase. However, the Polish National Health Fund data indicate that only 0,7% of women giving birth in the northern macro-region of Poland received diagnosis and help from public funds. In The Next Stop: Mum project, 250 women benefited from psychological consultations. Conclusion Increased severity of depression and anxiety symptoms during the pandemic indicates the need for additional psychological support for postpartum women. However, very few women are diagnosed in health facilities in the first year postpartum and thus are rarely referred for further treatment. The study shows that the availability of services and the focus on social and individual barriers may be critical factors in implementing perinatal mental health programs and practices. This may be especially needed in a country where the screening obligation is new. In case of a further pandemic, policymakers and health care professionals should be aware that the duration of the restrictions and the repetition of lockdowns are associated with the aggravation of symptoms. The online screening without the possibility to discuss the results is only partially effective in increasing referrals for possibly affected women.